2012
DOI: 10.1186/1475-2840-11-95
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis and screening of antidiabetic, antioxidant and hypolipidemic potential of Cinnamomum tamala oil in streptozotocin induced diabetes mellitus in rats

Abstract: Aim of the studyThis study was made to investigate the antidiabetic, antioxidant and hypolipidemic potential of Cinnamomum tamala, (Buch.-Ham.) Nees & Eberm (Tejpat) oil (CTO) in streptozotocin (STZ) induced diabetes in rats along with evaluation of chemical constituents.Materials and methodsThe GC-MS (Gas chromatography–mass spectrometry) analysis of the oil showed 31 constituents of which cinnamaldehyde was found the major component (44.898%). CTO and cinnamaldehyde was orally administered to diabetic rats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…However, contradictory results have been obtained for acute toxicity of CTEO. Kumar, Vasudeva, et al () reported that 2,000 mg/kg bw CTEO caused 50% mortality in male Wistar rats. Hence, the aim of the present study was to study for the first time sub‐chronic toxicity of CTEO, extracted from C. tamala leaves, in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, contradictory results have been obtained for acute toxicity of CTEO. Kumar, Vasudeva, et al () reported that 2,000 mg/kg bw CTEO caused 50% mortality in male Wistar rats. Hence, the aim of the present study was to study for the first time sub‐chronic toxicity of CTEO, extracted from C. tamala leaves, in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory results have been obtained for acute toxicity of CTEO. Kumar, Vasudeva, et al (2012b) (Kapoor et al, 2008). For decades, C. tamala and its leaves are being used in food and pharmaceutical preparation (Chanotiya et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic layer was separated out and absorbance was measured at 532 nm using double beam UV-visible spectrophotometer (systronics 2203, Bangalore, India) against a blank. MDA values are calculated using the extinction coeffi cient of MDA-thiobarbituric acid complex 1.56 × 105 l/mol × cm and expressed as N mol/ mg protein [ 14 ] .…”
Section: Estimation Of Mda Levelmentioning
confidence: 99%
“…In meta-analysis of observational studies until April 2014 in PubMed/Medline, an association between obesity and Vitamin D was found, irrespective of age, latitude and cut-offs to define vitamin D deficiency [22]. BMI was strongly associated with plasma 25(OH)D and PTH concentrations with possible contribution of plasma 25(OH)D in the pathogenesis of hypertriglyceridemia and atherogenic dyslipidemia through inflammation, because the association disappeared when uCRP (ultrasensitive C Reactive Protein) was introduced as covariable [9]. 25OHD low levels and unfavorable lipid patterns has been found in children too [25].…”
Section: Introductionmentioning
confidence: 99%